Modelling industrial new orders for the euro area - Gabe de Bondt; Heinz Christian Dieden; Sona Muzikarova; Istvan Vincze (European Central Bank (ECB), 2014)
This paper models industrial new orders across European Union (EU) Member States for various breakdowns. A common modelling framework exploits both soft data (business opinion surveys) and hard data (industrial turnover). The estimates show for about 200 cases that the model determinants significantly help in explaining monthly growth rates for new orders. An alternative estimation method, different model specifications and out-of-sample and real-time forecasting all show that the model results are robust. We present real-time outcomes of a European Central Bank (ECB) indicator on industrial new orders at an aggregated euro area level. This indicator is largely based on national new orders data and on estimates yielded by the model for those countries that no longer report new orders at the national level. Finally, we demonstrate the leading nature of the ECB indicator on euro area new orders in relation to industrial production.
Keywords: C22; C52; E32; 330; euro area; industrial new orders; Leading indicators; real-time analysis